Unveiling the digital classroom: Exploring students' perspectives on engaging online discussions in English language education at a private university in Yogyakarta - Endro Dwi Hatmanto; Bambang Widi Pratolo; Cahyo Baskoro; Sri Sudarsi (Universitas Ahmad Dahlan, 2023)
The integration of technology in education has transformed the teaching and learning of the English language. Online discussions had gained significant attention due to their potential to enhance students' linguistic proficiency, critical thinking skills, and overall engagement. However, there was a lack of research on students' perspectives on engaging in online discussions specifically within the context of English Language Education departments at private universities in Yogyakarta. This study aimed to address this gap by exploring students' experiences, perceptions, and challenges when participating in online discussions at a private university in Yogyakarta. The research investigated the benefits, drawbacks, and challenges encountered by students in online group discussions. A qualitative research methodology was employed, and data was collected through interviews with five English education students. The findings revealed that engaging in online discussions offered benefits such as increased interest, flexibility, improved preparation and performance, and enhanced writing skills. However, limitations included the loss of an authentic discussion experience, inadequate acquisition of detailed information, and frustration due to a lack of responses and comments. Challenges faced by students included low internet connection. The study contributed to the existing literature by shedding light on students' perspectives and informing pedagogical practices in the specific context of English Language Education in Yogyakarta's private universities.